Reflexões sobre a educação de surdos e o ensino de Libras-L1 a partir do Currículo da Cidade de São Paulo - Cruz, Marcia (2025)
Deaf education is a recurrent subject in this century and has, as its effect, the consolidation of bilingual approach as being the most adequate conception for the students´ teaching and learning. The bilingual process involving Libras (Brazilian Sign Languange), a visual-spacial language, and Portuguese, an oral-auditory one, is only taken into consideration in the written mode. It is understood that, for that process to occur in a satisfactory way, a solid linguistic basis in Libras, considered the native language, is necessary. This qualitative documental essay aims to reflect on the teaching of the deaf, dissecting the teaching of Libras as first language, with the goal of understanding its insertion in the school programme. We chose, as the source for the analysis, the document entitled Currículo da cidade: Educação Especial: Língua Brasileira de Sinais (City curriculom : Special Educationa: Brazilian Sign Language) of São Paulo city. The choice was due to it being a pioneer in the federal level. We intend to investigate and reflect about deaf education, acquisition and learning of the sign language by the deaf and the conception of a school programme, in order to understand the Libras Programme's contribution to the education of the deaf aiming to better understand in which way the referred conceptionsreveal themselves in the Currículo da Cidade: Educação Especial: Língua Brasileira de Sinais of São Paulo city.